Sensing of Inorganic Ions and Organic Molecules Using Fluorescence and Plasmonic Nanomaterials - Kainth, Shagun (My University, 2020)
Nanomaterials are the emerging star in the field of sensor for the determination of various toxins and biomolecules. The SPR and Fluorescence active nanomaterials attained wide scope due to their fast response towards the external moieties. Thesis involves various segments i.e. synthesis of different size AuNPs and surface passivated carbon dots (C-dots). The morphology and surface composition of nanomaterials were characterized by HRTEM, FTIR and XPS. These materials were used to sense various metal ions (such as Fe+3, F-, Cu+2 ions etc.) and biomolecules like picric acid (PA), thiopurines and creatinine respectively. Large AuNPs exhibited high selectivity for thiopurines with LOD = 0.0001mM. The surface passivation in C-dots modulates its quantum yield (58-30%) and average lifetime (~2.2 ns). The C-dots enriched with pyrrolic and pyridinic moieties exhibited high selectivity for creatinine with LOD = 36 nM whereas C-dots prepared from citrus limetta showed effective response for F- ions.
Keywords: Sensor; C-dots; AuNPs; Nitrogen surface passivation; Turn off-on mechanism; Logic gate